The praxis of responsible investment in South Africa: a holistic case study of Evolution One Fund - Zaulochnaya Ya-Brouwer, Irina (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
At the beginning of the 21st century the public interest in environmental and social sustainability, and corporate governance grew exponentially fuelled by recurring ecological and financial crises. The market demand for cleaner production and corporate transparency created opportunities for sustainability entrepreneurs in a variety of industries, including financial markets and investment management. An increasing number of financial institutions across the world now offer ethical or socially responsible products to meet the environmental, social and governance (ESG) aspirations of their clients. In the US, according to the Social Investment Forum (SIF), responsible investment (RI) assets reached US$ 2,29 trillion in 2007 (Mitchell, 2008). The European Sustainable Investment Forum (EuroSIF) estimated that total European SRI assets reached EUR 5 trillion in 2009 (Wheelan, 2010). In June 2011 the International Finance Corporation (IFC) reported that at the end of 2010 professional sustainable investment under management in South Africa approximately equalled US$ 122,6 billion (IFC, 2011:44). The statistics describing the rapid growth in the ESG-type investments are, however, complicated by the variety of names and definitions used to describe this emerging type of investment and a general market uncertainty about what constitutes the practice of RI. The purpose of this case study is to better understand responsible investment principles and practice as seen through the eyes of a South African private equity fund, which specializes in clean technology.
Keywords: Social responsibility of business -- South Africa; Investments -- Moral and ethical aspects -- South Africa; Institutional investments -- Moral and ethical aspects -- South Africa; Private equity funds -- South Africa